Comparative mitochondrial genome analysis of Dendrolimus houi (Lepidoptera: Lasiocampidae) and phylogenetic relationship among Lasiocampidae species - Han, Xiaohong (PLoS One, 2020)
Dendrolimus houi is one of the most common caterpillars infesting Gymnosperm trees, and widely distributed in several countries in Southeast Asia, and exists soley or coexists with several congeners and some Lasiocampidae species in various forest habitats. However, natural hybrids occasionally occur among some closely related species in the same habitat, and host preference, extreme climate stress, and geographic isolation probably lead to their uncertain taxonomic consensus. The mitochondrial DNA (mtDNA) of D. houi was extracted and sequenced by using high-throughput technology, and the mitogenome composition and characteristics were compared and analyzed of these species, then the phylogenetic relationship was constructed using the maximum likelihood method (ML) and the Bayesian method (BI) based on their 13 protein-coding genes (PCGs) dataset, which were combined and made available to download which were combined and made available to download among global Lasiocampidae species data. Mitogenome of D. houi was 15,373 bp in length, with 37 genes, including 13 PCGs, 22 tRNA genes (tRNAs) and 2 rRNA genes (rRNAs). The positions and sequences of genes were consistent with those of most known Lasiocampidae species. The nucleotide composition was highly A+T biased, accounting for ~80% of the whole mitogenome. All start codons of PCGs belonged to typical start codons ATN except for COI which used CGA, and most stop codons ended with standard TAA or TAG, while COI, COII, ND4 ended with incomplete T. Only tRNA(Ser (AGN)) lacked DHU arm, while the remainder formed a typical “clover-shaped” secondary structure. For Lasiocampidae species, their complete mitochondrial genomes ranged from 15,281 to 15,570 bp in length, and all first genes started from trnM in the same direction. And base composition was biased toward A and T. Finally, both two methods (ML and BI) separately revealed that the same phylogenetic relationship of D. spp. as ((((D. punctatus + D. tabulaeformis) + D. spectabilis) + D. superans) + (D. kikuchii of Hunan population + D. houi) as in previous research, but results were different in that D. kikuchii from a Yunnan population was included, indicating that different geographical populations of insects have differentiated. And the phylogenetic relationship among Lasiocampidae species was ((((Dendrolimus) + Kunugia) + Euthrix) + Trabala). This provides a better theoretical basis for Lasiocampidae evolution and classification for future research directions.